GROUP COUNSELING: A REALITY APPROACH TO INCREASED RESILIENCE STUDENT ACADEMICS - Roikhatun Naimah; Arifin Nur Budiono; Yurike Khinanty Karamoy (Sahabat Publikasi, 2023)
As students are inseparable from learning and assignments with the many tasks given by the teacher resulting in students experiencing pressure this event is called academic resilience. The purpose of this study was to determine the effect of reality approach group counseling on increasing the academic resilience of students of SMK Negeri 2 Jember. The research method used is an experimental type. The conclusion from this study is that group guidance can have an impact on the level of student academic resilience. This can be proven from the results of the pretest and posttest after group counseling. In addition, the factors that affect academic resilience include: Internal factors that are typical in Indonesia are gratitude, psychological contract and religiosity. External factors identified were the quality of the student-teacher relationship and parenting style, peer social support, and general social support.